Equilibrium and kinetic mechanisms of woody biochar on aqueous glyphosate removal. (February 2016) - Mayakaduwa, S.S.; Kumarathilaka, Prasanna; Herath, Indika; Ahmad, Mahtab; Al-Wabel, Mohammed; Ok, Yong Sik; Usman, Adel; Abduljabbar, Adel; Vithanage, Meththika
Abstract: We investigated the removal of aqueous glyphosate using woody (dendro) biochar obtained as a waste by product from bioenergy industry. Equilibrium isotherms and kinetics data were obtained by adsorption experiments. Glyphosate adsorption was strongly pH dependent occurring maximum in the pH range of 5–6. The protonated amino moiety of the glyphosate molecule at this pH may interact with π electron rich biochar surface via π–π electron donor–acceptor interactions. Isotherm data were best fitted to the Freundlich and Temkin models indicating multilayer sorption of glyphosate. The maximum adsorption capacity of dendro biochar for glyphosate was determined by the isotherm modeling to be as 44 mg/g. Adsorption seemed to be quite fast, reaching the equilibrium <1 h. Pseudo-second order model was found to be the most effective in describing kinetics whereas the rate limiting step possibly be chemical adsorption involving valence forces through sharing or exchanging electrons between the adsorbent and sorbate. The FTIR spectral analysis indicated the involvement of functional groups such as phenolic, amine, carboxylic and phosphate in adsorption. Hence, a heterogeneous chemisorption process between adsorbate molecules and functional groups on biochar surface can be suggested as the mechanisms involved in glyphosate removal. Highlights: A waste byproduct of a bioenergy industry was used for glyphosate remediation. Maximum glyphosate removal at pH 5–6 due to electron donor–acceptor interactions. Rate limiting step may be chemisorption through sharing or exchange of electrons. Phenolic, amine, and carboxylic functional groups were involved in adsorption.